DISPARITAS DALAM PELAKSANAAN HUKUM ATAS PENYELESAIAN ISU-ISU PERKAWINAN YANG DIHADAPI PENGHULU DI KABUPATEN MUARA ENIM SUMATERA SELATAN - adrianto; Haslinda (EL-ADABI : Jurnal Studi Islam, 2025)
This study aims to describe Increasing what is the disparity in the application of law regarding the resolution of marital issues faced by the Penghulu In Muara Enim Regency, South Sumatra the data collection technique is using library research or library study research with data collection techniques carried out by examining literature, document, and other sources of information related to the Topik of researchers. The result of this study: the first, resolution of marital legal issues among the chiefs In Muara Enim Regency, as early marriage and marriage registration requires a comprehensive approach. This involves education, personal approach, cooperation with various parties and a good understanding of the law. The second, Penghulu Ii Muara Enim Regency Like other regions, facing various obstacles regarding marriage law issues Some of these obstacles include a lack of village head personnel. Especially in remote areas, and the challenges complex application of marriage law and sometimes contrary to local customs. The third, Penghulu In Muara Enim Regency, South Sumatra facing obstacles in carrying out his duties disparity (difference) in legal sources used.